Utilization of the validated Psoriasis Epidemiology Screening Tool to identify signs and symptoms of psoriatic arthritis among those with psoriasis: a cross‐sectional analysis from the US‐based Corrona Psoriasis Registry. (5th March 2019) - Mease, P.J.; Palmer, J.B.; Hur, P.; Strober, B.E.; Lebwohl, M.; Karki, C.; Reed, G.W.; Etzel, C.J.; Greenberg, J.D.; Helliwell, P. S.
Abstract: Background: Despite increasing awareness of the disease, rates of undiagnosed psoriatic arthritis (PsA) are high in patients with psoriasis (PsO). The validated Psoriasis Epidemiology Screening Tool (PEST) is a five‐item questionnaire developed to help identify PsA at an early stage. Objectives: To assess the risk of possible undiagnosed PsA among patients with PsO and characterize patients based on PEST scores. Methods: This study included all patients enrolled in the Corrona PsO Registry with data on all five PEST questions. Demographics, clinical characteristics and patient‐reported outcomes were compared in Corrona PsO Registry patients with PEST scores ≥3 and <3 using t ‐tests for continuous variables and chi‐squared tests for categorical variables; scores ≥3 may indicate PsA. Results: Of 1516 patients with PsO, 904 did not have dermatologist‐reported PsA; 112 of these 904 patients (12.4%) scored ≥3 and were significantly older, female, less likely to be working, and had higher BMI than patients with scores <3. They also had significantly longer PsO duration, were more likely to have nail PsO and had worse health status, pain, fatigue, Dermatology Life Quality Index and activity impairment. Conclusions: Improved PsA screening is needed in patients with PsO because the validated PEST identified over one‐tenth of registry patients who were not noted to have PsA as having scores ≥3, who could have had undiagnosed PsA. Appropriate, earlier care is important because these patients were more likely to have nail PsO, worse health‐related quality of life and worse activity impairment.